Interprofessional collaborative practice in health and social care for people living with multimorbidity: a scoping review protocol - Josephine-L. K. Murray; Virginia Hernandez-Santiago; Frank Sullivan; Joanna Hornal; Farhana Badshah; Ben Keatley; Jillian Galbraith; Pam Channer; Anne Fearfull; Anne Haddow; Eleanor Johnston; Maureen Ward; et al. (Systematic Reviews)
Abstract Background Multimorbidity, the co-existence of two or more conditions within an individual at any one time, is globally increasing and forecasted to rise. This poses a significant challenge for current models of healthcare delivery, which are now ill-equipped to meet the future population health needs. Interprofessional collaborative practice is a specific way professionals work closely together and with patients and their families to improve patient outcomes. Evidence suggests it can improve outcomes for people living with a single condition. What remains unknown is if interprofessional collaborative practice has been used to improve the outcomes of people living with multimorbidity, and if so, to what extent? Methods A scoping review is proposed to identify prior peer-reviewed research and grey literature related to interprofessional collaborative practice for multimorbidity in health and social care settings. A search strategy will identify primary, peer-reviewed research and grey literature. An initial limited search will be conducted to identify relevant existing systematic reviews. Their methods will be examined and their search terms scrutinised. A second comprehensive search will be used to interrogate four databases, looking back 10 years, seeking articles published in English, French, Spanish or Portuguese. Hand searching will be performed on all included full-text articles for any articles missing from the two steps above. Critical data will be extracted by adapting existing data abstraction forms based on the needs of the research objectives. These forms will be piloted before use. The results will be analysed descriptively. If appropriate, qualitative content analysis may be undertaken. Where sufficient numbers of homogeneous interventions exist, meta-analysis techniques will be applied. Results will be presented in tabular, graphic, and diagrammatic information displays. Discussion This scoping review will provide an overview of the current evidence base of interprofessional collaborative practice used internationally for people living with multimorbidity in health and social care settings. These findings will provide valuable information to improve health and social care practice as well as change systems and policy to meet the population need of multimorbidity. Systematic review registration: The protocol was submitted to Open Science Framework on 19 December 2023 and registered on OSF Registries. Registration DOI: https://doi.org/10.17605/OSF.IO/UXHG3 .